Abundance of Soil Mites (Arachnida: Acari) in a Natural Soil of Central Argentina - Bedano, José Camilo (2005)
Despite the potential ecological importance of mites (Acari) in uncultivated soils adjacent to cultivated plots, basic information on the occurrence of these soil microarthropods in such sites is scarce, especially in South American agroecosystems. In this paper, we describe the mite fauna in an uncultivated soil adjacent to crop fields in central Argentina. Densities of major mite taxa were examined in soil of an undisturbed and uncultivated plot in the La Colacha Basin, Argentina, at bimonthly intervals over 2 yrs. Oribatida, Mesostigmata, and Astigmata meanabundances were rather low compared with values obtained in similar environments, while Prostigmata density was similar to those recorded in other studies. The Oribatida and Mesostigmata were the most-abundant taxa, followed by the Prostigmata and Astigmata. Temporal variations in soil mite density were consistent with the general trend of the greatest mite abundance occurring in spring and summer and the lowest in winter. These findings are compared with the results from other studies, and their ecological implications are discussed. This study provides important information on soil mite populations in natural soils and indicates that such natural soil refuges adjacent to cultivated soils can provide baseline data for studies of bioindicators of soil quality.